Abordagem interdisciplinar no ensino da física térmica em um curso técnico em edificações a partir da construção de um forno solar - Silva, Jonas Cegelka da (2018)
Aiming to foment actions toward the interdisciplinarity focus, this investigation was structured in order to make converge the subjects of physics and building comfort of the second year of the technical course in buildings, integrated with the High School in the Instituto Federal de Educação, Ciência e Tecnologia Farroupilha (Farroupilha Federal Institute of Education, Science and Technology), Campus Santa Rosa. In the theoretical course, the work was based on the theories of the conceptual fields, of meaningful learning, of critical meaningful learning, in the interdisciplinarity and in the integrated curriculum. The research, which is qualitative and descriptive, sought to answer the following question: what are the implications of an interdisciplinary work, having as a motivating element the construction of a solar oven in order to provide a meaningful learning experience to the students in the matter of thermal physics concepts and of the thermal properties of materials? In the search for answers to the question, our main goal was to investigate the meaningful learning process of the students for the conceptual field of thermal physics and of the thermal properties of the materials by means of teaching strategies that comprehend both the construction of a low-cost solar oven and the implementation of an interdisciplinary evaluation coherent with our pedagogic practice. The investigation comprehended two studies: one in the first semester of 2016 and, another, in the first semester of 2017. In both cases, we had as data collection instruments, questionnaires for the identification of students' previous conceptions about the concepts of thermal physics, questions about these concepts closer to their every day lives, the construction of solar ovens starting from situations that guide the search for the best materials to be utilized, conceptual maps built by the students regarding the prototypes, as well as an interdisciplinary evaluation about the main convergent concepts of both subjects. As results, we gathered evidences of meaningful learning of the main concepts involved, and also of procedural and attitudinal contents regarding the process of building the oven. It motivates us to keep improving the proposal, as well as developing more interdisciplinary works.